2023
DOI: 10.20944/preprints202308.0032.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Vivo Assessment of Acute Toxicity and Immunotoxicity of Quantum Dots with Different Physicochemical Properties

Evgeniia Gerasimovich,
Svetlana Bozrova,
Maria Baryshnikova
et al.

Abstract: Fluorescent semiconductor nanocrystals called quantum dots (QDs) have gained attention in biomedical applications, including imaging, molecular tracking, and drug delivery, due to their unique optical properties. However, their use is limited because of safety issues. This study was aimed at assessment the acute toxicity of QDs with different core chemical compositions and surface charges in mice. In addition, the immunotoxicity of CdSe/ZnS QDs was estimated. CdSe/ZnS, PbS/CdS/ZnS, and CuInS2/ZnS QDs were synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The histopathological analysis indicated the most significant morphology changes in the kidney and liver tissues and immunopositivity for TNF-α 6 h after SiQDs administration, the degree of modification being dependent on the dose tested. Regarding the extent of inflammation over time, Gerasimovich et al [ 49 ] showed that the serum level of the majority of pro-inflammatory cytokines, including TNF, was similar to that of control 7 days after injection with CdSe/ZnS QDs, suggesting that the immune reaction to QDs is reversible. Hepatic impairments, such as disordered hepatic cords and enlarged central veins, were also detected after CdSe QDs administration [ 43 ], and apoptotic and necrotic cells with an increased level of TNF-α were previously shown after only 6 mg/kg of b.w.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological analysis indicated the most significant morphology changes in the kidney and liver tissues and immunopositivity for TNF-α 6 h after SiQDs administration, the degree of modification being dependent on the dose tested. Regarding the extent of inflammation over time, Gerasimovich et al [ 49 ] showed that the serum level of the majority of pro-inflammatory cytokines, including TNF, was similar to that of control 7 days after injection with CdSe/ZnS QDs, suggesting that the immune reaction to QDs is reversible. Hepatic impairments, such as disordered hepatic cords and enlarged central veins, were also detected after CdSe QDs administration [ 43 ], and apoptotic and necrotic cells with an increased level of TNF-α were previously shown after only 6 mg/kg of b.w.…”
Section: Discussionmentioning
confidence: 99%